Antimicrobial sensitivity pattern of Salmonella typhi isolated from blood culture in a referral hospital - Hasan, Bulbul; Nahar, Sabera Gul; Akter, Laila; Saleh, Ahmed Abu (Bangladesh Journal of Medical Microbiology, 2011)
The present study has been carried out in an attempt to evaluate antimicrobial susceptibility patterns with special reference to susceptibility of Salmonella Typhi to ciprofloxacin isolated from blood culture. The study is also designed to find out the MIC of Ciprofloxacin by E- test. Blood samples were taken for culture sensitivity, Widal test and ICT from 100 clinically suspected cases of typhoid fever in 1st week of illness who attended at out patient department of Rajshahi Medical College Hospital (RMCH).The study was done in Microbiology Department of Rajshahi Medical College and Shishu Hospital, Dhaka. Diagnosis of patients was based on history of fever, blood culture, Widal test and ICT. The antimicrobial susceptibility pattern of isolates from blood culture was recorded. Further more, the minimum inhibitory concentration of Ciprofloxacin was determined by E-test for the isolates resistance to Ciprofloxacin. Out of 100 suspected cases of typhoid fever, blood culture positive for S. Typhi were 16 (16%). Antimicrobial susceptibility pattern of 16 isolates of S. Typhi showed that no isolate was resistant to Ceftriaxone and Ceftazidime, only 03(18.75%) were resistant to Ciprofloxacin and Azithromycin whereas 10(62.5%) were MDR showing resistance to Ampicillin, Co-trimoxazole and Chloramphenicol which are first-line antityphoidal drugs. On the other hand, all (100%) the isolates were resistant to Nalidixic acid. The study revealed that Ceftriaxone and Ceftazidime are the most effective drugs in the treatment of typhoid fever. Moreover, E-test has been found to be helpful to determine appropriate therapeutic dose of Ciprofloxacin especially in case of drug resistance and pediatric population. DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15816 Bangladesh J Med Microbiol 2011; 05 (01): 16-20